Attitudes and knowledge about contraceptive use of saudi married women: a cross-sectional study approach (Bioscience Journal, 2023)
The speedy change in the Saudi Arabian community's socio-demographic pattern will significantly influence reproductive attitudes and practices with increasing preferences toward family planning because of the use of contraceptives. The current study was conducted to determine the attitudes and knowledge of married women in the Aseer region of Saudi Arabia regarding contraceptives use. Saudi married women from the Aseer region were the participants of this cross-sectional study. The study's objectives were covered via a standardized questionnaire, and the study comprised of 412 married women. A 100 % participant’s response was demonstrated, while 31.8 % of the respondents were 31-40 years old. Most of the participants have a great awareness and knowledge about contraceptives, while (n=324; 78.6%) had previously used contraceptives. Additionally, 297 (72.1%) have intention to use contraceptive methods in the future. Majority of the participants (n=297; 91.6%) considered the economic and family planning as a reason for using the contraceptives, while natural family planning was mostly preferred (n=202; 49%). Logistic regression analysis exhibited significant correlation between the age, education, employment, monthly income and children number. The findings show that Saudi married women have high perceptions and knowledge of contraception. However, more effort is required to raise awareness regarding family planning and contraceptives, whereas the policy makers must exclude the obstacles to women from using contraceptives.